Optimalisasi Pemanfaatan Candi Brahu sebagai Tempat Ritual Keagamaan Umat Buddha - Sukarti, Sukarti; Restu Waisaka, Gerry (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
Candi Brahu is one of the significant relics of the Classical Period in East Java that holds deep spiritual value for the Buddhist community. However, its utilization as a site for religious rituals remains suboptimal. This study aims to: (1) analyze the spiritual values of Candi Brahu within the context of Buddhism; (2) identify the obstacles in utilizing Candi Brahu for Buddhist religious rituals; and (3) analyze strategies to optimize the use of Candi Brahu for Buddhist religious practices. This qualitative research employs a case study approach conducted in Mojokerto Regency, focusing on Candi Brahu. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. Data validity was tested through technique and source triangulation. The results show that the spiritual values of Candi Brahu encompass aspects of enlightenment (Bodhi), inner serenity (Samma Sati), and wisdom (Paññā), reflecting the core teachings of Buddhism. The main obstacles to its utilization include limited infrastructure, weak institutional coordination, and insufficient public dissemination. Optimization strategies are directed toward revitalizing ritual facilities, strengthening community-based institutions, and integrating Candi Brahu into the national Buddhist pilgrimage network. The sustainable and living heritage approach aims to ensure that Candi Brahu remains not only physically preserved but also thrives as a living spiritual and cultural space for Buddhists.